Analisis Efisiensi Teknis, Alokatif dan Ekonomi pada Usahatani Padi Sawah - Zulkarnian Zulkarnain; Djoko Umar Said; Deka Amitasari (Penerbit Goodwood, 2022)
Purpose: Research objectives: the effect of input factors for lowland rice farming production, and technical efficiency, allocative, and economic use of lowland rice farming inputs. Method: The population is 908 farmers and the sample is taken using Sugiart's calculation, which obtained 51 samples by determining the sample by simple random sampling. Multiple linear regression analysis with Cobb-Douglas production function, technical efficiency analysis with DEA ??approach, allocation efficiency analysis and economic efficiency analysis. Results: 1) land area production factor, phonska fertilizer and KCL fertilizer significantly affect rice farming production, 2) technical efficiency value of 0.856, 3) allocative efficiency value of 2.72, 4) economic efficiency value of 2.32 . Conclusions: Lowland rice farming is not efficient in terms of technical efficiency, allocative efficiency and economic efficiency.